Phylogenetic relationships and comparative larval morphology of epigean and stygobitic species of Limbodessus Guignot, 1939 (Coleoptera: Dytiscidae: Bidessini), with a key of identification - Michat, Mariano Cruz (2012)
The larvae of five epigean and 25 stygobitic species of the diving beetle genus Limbodessus Guignot, 1939 are described and illustrated for the first time, with special emphasis on morphometry and chaetotaxy of the cephalic capsule, head appendages, legs, last abdominal segment and urogomphi. Those of the following five epigean species are described: L. amabilis (Clark, 1862), L. compactus (Clark, 1862), L. inornatus (Sharp, 1882), L. praelargus (Lea, 1899), L. shuckardii(Clark, 1862). The 25 stygobitic larvae described are: L. barwidgeeensis Watts & Humphreys, 2006, L. bigbellensis(Watts & Humphreys, 2000), L. challaensis (Watts & Humphreys, 2001), L. cooperi Watts & Humphreys, 2006, L. eberhardi (Watts & Humphreys, 1999), L. exilis Watts & Humphreys, 2006, L. fridaywellensis (Watts & Humphreys, 2001), L. hillviewensis (Watts & Humphreys, 2004), L. hinkleri (Watts & Humphreys, 2000), L. leysi Watts & Humphreys, 2006, L. macrohinkleri Watts & Humphreys, 2006, L. masonensis (Watts & Humphreys, 2001), L. millbilliensis Watts & Humphreys, 2006, L. mirandaae Watts & Humphreys, 2006, L. morgani (Watts & Humphreys, 2000), L. nambiensisWatts & Humphreys, 2006, L. ordinarius Watts & Humphreys, 2009, L. palmulaoides Watts & Humphreys, 2006, L. pulpa (Watts & Humphreys, 1999), L. raeae Watts & Humphreys, 2006, L. raesideensis (Watts & Humphreys, 2001), L. windarraensis (Watts & Humphreys, 1999), L. yandalensis Watts & Humphreys, 2006, L. yarrabubbaensis Watts & Humphreys, 2009, L. yuinmeryensis (Watts & Humphreys, 2003). The morphology and chaetotaxy of epigean vs. stygobitic species are compared, and a key for the identification of the species is presented. Contrary to their epigean counterparts, larvae of stygobitic Limbodessus have turned out to be very divergent morphologically. In addition to the common characteristics associated with an underground living (i.e., absence of stemmata, reduced pigmentation, and thin or soft exoskeleton), larvae of these species have undergone a variable modification of the frontoclypeus and have evolved relatively shorter tarsal claws. Two morphological groups of stygobitic species are evident, one including species less deviated from the ancestral (epigean) condition and another group comprising more modified species that typically have a larger size, a more or less pyriform head with a digitiform nasale, and a strongly reduced occipital foramen. Primary chaetotaxy of the species has remained a very conservative expression of the phenotype. Secondary chaetotaxy shows variation among the species, the most obvious being the variable number of lamellae clypeales and the presence or absence of secondary setae on the urogomphus. The phylogenetic relationships of Limbodessus are analyzed cladistically. Larvae of this genus lack the primary pore ABc, which is a synapomorphy of the tribe Bidessini. As presently defined, Limbodessus is probably paraphyletic with respect to Allodessus Guignot, 1953.